2022
DOI: 10.21203/rs.3.rs-1653897/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

MiR-128-1-5p inhibits cell proliferation and induces cell apoptosis via targeting PRKCQ in colorectal cancer

Abstract: Background MicroRNAs (miRNAs) are a type of highly conserved and endogenous noncoding RNA which can regulate various cellular processes, including cell proliferation, differentiation, apoptosis, migration and metastasis. Aberrant expression of miR-128-5p, has been shown to be a key regulator in tumorigenesis and cancer development. But the role and the underlying molecular mechanisms of miR-128 in CRC still remain largely unknown. Methods The expression and clinical significances of miR-128-1-5p in colorecta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Our group established a rat model in the early stage [29]. Through screening, we found that there were differential expressions of the microRNAs (miRNAs).…”
Section: Cowshed Pm25-stimulated Upregulation Of Mir-122-5pmentioning
confidence: 99%
“…Our group established a rat model in the early stage [29]. Through screening, we found that there were differential expressions of the microRNAs (miRNAs).…”
Section: Cowshed Pm25-stimulated Upregulation Of Mir-122-5pmentioning
confidence: 99%
“…In this study, using the in vivo rat infection model constructed by our group, we found that miR-212-5p was differentially expressed based on transcriptome data analysis [ 35 ], and ARAF was also predicted as its target gene through bioinformatic analyses. We investigated the mechanism of miR-212-5p-targeted ARAF in PM 2.5 -induced apoptosis of rat alveolar macrophages in vitro, aiming to provide gene therapy targets and a scientific basis for PM 2.5 -induced apoptosis triggering respiratory diseases at the level of miRNA regulation.…”
Section: Introductionmentioning
confidence: 99%